Technology Based Employees Training and Organizational Performance as Perceived by Employees - Humayoun, Asad Afzal; ., Kashif Ur Rehman (Information Management and Business Review, 2013)
The present study explores the nature of the technology-based HR trainings practices with a focus on the banking sector in Pakistan. The study was carried out in the twin-cites of Rawalpindi and Islamabad. Random sampling technique was adopted and population mainly was categorized into six Islamic banks and 6 conventional Banks. The study recommends that by implementing the technology-based training and acquiring the inputs from the top level management and the internal customers using this input and information for the organizational strategies and goal, can further the market shares and the profitability.